2014
DOI: 10.14740/jocmr1865w
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Patients After an Acute Coronary Event: Hospital Discharge

Abstract: BackgroundThe acute coronary syndrome (ACS) has a high morbi-mortality rate, including physical deficiencies and functional limitations with impact on quality of life. Cardiovascular rehabilitation 1 (CVR1) should begin as early as possible, to enable improvement in functional capacity and quality of life. Previous studies have shown association of cardiovascular diseases with quality of life, in which depression and anxiety are the domains most altered. The aim of the study is to verify the impact of an acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
2
6
0
2
Order By: Relevance
“…Consequently, findings showed that male patients scored higher QoL than female patients. This result is consistent with other studies (33,34). Female patients usually show lower level of coping with illness compared to male patients and they use different coping mechanism (35).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consequently, findings showed that male patients scored higher QoL than female patients. This result is consistent with other studies (33,34). Female patients usually show lower level of coping with illness compared to male patients and they use different coping mechanism (35).…”
Section: Discussionsupporting
confidence: 93%
“…The ACS clinical presentations (e.g. chest pain and shortness of breath) directly affect patients' ability to perform tasks related to daily life activities such as working (33). Consequently, the perception of inability to work among non-working patients may affect their lifestyle and their self-image, and hence their QoL.…”
Section: Discussionmentioning
confidence: 99%
“…The most common comorbidities were hypertension (56.15%) and diabetes (29.23%) among ACS patients. These results were similar to the studies conducted by Negi PC et al and Mohanan PP et al, Azmi et al 9,10,12 which reports as 43.4%, 48.4% and 61.5% of hypertension and 17.7%, 37.6% and 29.8% of diabetes in the ACS population respectively. In the present study, family history of patients did not have much role in the occurrence of ACS.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, prescriptions with antianxiety drugs were more indicating higher anxiety level among the patients. This was in favour of the study by Dias et al, 9 which implies that there is higher level of anxiety among the patients considered for ACS studies. The reason for this may be the insecurity of the patient after the occurrence of the disease.…”
Section: Discussionmentioning
confidence: 79%
“…As for the study that described the test [8], the Borg scale was shown to be easy to apply, making it possible to evaluate the improvement in functional capacity. It is worth emphasizing that the perceived exertion rate was also influenced by psychological and not physiological factors only, thus making it difficult to define which variable was predominant [22].…”
Section: Discussionmentioning
confidence: 99%